A PALYNOLOGICAL STUDY RELATING TO THE TORONTO FORMATION - Terasmae, Jane (My University, 1955)
The aim of this study Is to establish the age of the Toronto formation* The investigation was planned in three parts; the first dealing with field work and analytical methods, the second with fundamental pollen morphology, and the third with implications of palynological studies in related fields. The warn climate beds of the Toronto formation were found to be of the Sangamon age, Methods have been developed for exploring Pleistocene sediments, other than peat, for microfossils